Innovation and skills: implications for the agri-food sector. Issue 4 (6th May 2014) - Jack, Claire; Anderson, Duncan; Connolly, Niamh
Abstract : Purpose: – Despite the economic downturn, the Northern Ireland agri-food sector has remained resilient experiencing export growth, particularly in emerging economies. The sector recognises that to maintain its competitive advantage in both existing and new markets it will require a business strategy focused on product, service and process innovation. The purpose of this paper is to explore how firms within the sector consider how this will impact upon future skills and training needs and identifies where the industry considers the appropriate policy interventions are required. Design/methodology/approach: – A survey was undertaken to explore how innovation and technology adoption within the agri-food and drinks sector is impacting on educational and skills requirements. In total, 30 companies were interviewed, providing representation from all the food and drinks sub-sectors and covering at least 50 per cent of employee numbers in each sub-sector. The survey focuses on current and future skills requirements for specific cohorts of employees in the sector; specifically those who have undertaken further full-time training beyond minimum school leaving age. In addition, it aimed to seek employer feedback on those entering the labour market for the first time. Findings: – The results support the need for strong intermediate levels of educational attainment. In addition, the acquisition of work-related generic skills is essential for creating a more "flexible" and multi-skilled workforce. Up-skilling programmes, particularly for lower to mid-level management roles, will become increasingly important in the future. Experience gained through work placement and vacation and weekend work is viewed very positively. Companies expressed a greater need for engagement between the further and higher education sectors and industry in relation to the content, design and delivery of educational programmes to adequately meet the needs of the sector. Originality/value: – At a time when government is looking to growth in the private sector to stimulate economic growth in the wider economy, this paper highlights the skills and training challenges which have emerged within the Northern Ireland agri-food sector, in response to business strategies which are more focused on product, service and process innovation.